1978
DOI: 10.1056/nejm197811302992202
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Type II Collagen in Relapsing Polychondritis

Abstract: Relapsing polychondritis is a disorder of unknown cause characterized by the destruction of cartilage. To test the hypothesis that immunologic mechanisms are involved in the pathogenesis of relapsing polychondritis, we analyzed the serum of 15 patients for the presence of antibodies to cartilage. Antibodies to Type II (cartilage) collagen were found in the serum of five patients at the time of acute symptoms. No antibodies were detected either to cartilage proteoglycan or to other collagen types. The antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
2
9

Year Published

1981
1981
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(183 citation statements)
references
References 32 publications
4
156
2
9
Order By: Relevance
“…Inflammatory arthritis, with destruction and erosion of articular cartilage, is associated with the development of autoimmunity to type I1 cartilage collagen (1)(2)(3)(4)(5)(6)(7)(8) and to cartilage proteoglycan (3)(4)(5)(9)(10)(11)(12), and this may be related to the immunopathology of the disease. The immunity expresses itself through both the production of autoantibodies and the development of T cell-mediated cellular immunity.…”
mentioning
confidence: 99%
“…Inflammatory arthritis, with destruction and erosion of articular cartilage, is associated with the development of autoimmunity to type I1 cartilage collagen (1)(2)(3)(4)(5)(6)(7)(8) and to cartilage proteoglycan (3)(4)(5)(9)(10)(11)(12), and this may be related to the immunopathology of the disease. The immunity expresses itself through both the production of autoantibodies and the development of T cell-mediated cellular immunity.…”
mentioning
confidence: 99%
“…Pathophysiologic mechanisms clearly involve humoral and cell-mediated immune responses. A typical, but far from specific, finding is the presence of anti-type I1 collagen antibodies in the majority of patients (20)(21)(22). Some authors have found evidence of cell-mediated immune responses directed toward cartilage components (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…A policondrite estaria relacionada a anticorpos ao colágeno do tipo II presente nas cartilagens, no trato uveal e na notocorda, porém não no sistema nervoso central maduro 9,16,20 . Estes anticorpos têm sido encontrados em indivídu-os nas crises agudas de policondrite 16,20,21 . A susceptibilidade à doença parece também estar relacionada aos antígenos do complexo HLA-DR4 22,23 .…”
Section: Três Ou Mais Características Presentes E Confirmação Por Bióunclassified